Trichocystatin-2 from Trichomonas vaginalis: role of N-terminal cysteines in aggregation, protease inhibition, and trichomonal cysteine protease-dependent cytotoxicity on HeLa cells - Aranda-Chan, Verónica; Gutiérrez-Soto, Montserrat; Flores-Pucheta, Claudia Ivonne; Montes-Flores, Octavio; Arroyo, Rossana; Ortega-López, Jaime (Frontiers in Parasitology, 2025)
Trichomonas vaginalis is a protozoan parasite that causes trichomoniasis, the most common nonviral neglected sexually transmitted disease worldwide. Biomarkers and therapeutic targets, including specific trichomonad cysteine proteases (CPs) and their endogenous inhibitors, have been identified to diagnose and treat this disease. Trichocystatin 2 (TC-2) was previously identified as one of the three endogenous inhibitors of the parasite’s cathepsin L-like CPs, including TvCP39, which is involved in T. vaginalis cytotoxicity and is a potential therapeutic target. TC-2 contains five cysteines, including four located in the N-terminal sequence. These cysteines may be responsible for the formation of multimers of the recombinant protein expressed in E. coli. To determine whether these cysteines are responsible for the formation of TC-2 multimers and the effect of the N-terminus on CP inhibition, a recombinant TC-2 mutant was expressed, purified, characterized, and compared with the recombinant wild-type TC-2 protein. In silico and experimental analyses revealed that wild-type and mutant TC-2 proteins presented similar results in terms of secondary and tertiary structure prediction and high thermal stability. However, compared with that of wild-type TC-2, multimer formation was significantly reduced in the mutant lacking the four N-terminal cysteines, leading to a significant reduction in papain inhibition but not in trichomonal CP activity. These results support the hypothesis that the four cysteines located in the N-terminal region are responsible for aggregation, and their deletion affected the interaction of TC-2 with papain without affecting its inhibitory activity on homologous target proteases that are crucial for T. vaginalis virulence. Our results provide essential data supporting the use of TC-2 as a potential therapeutic target.